2020
DOI: 10.21203/rs.3.rs-33322/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacy Preparedness and Response for the Prevention and Control of COVID-19 in Aksum, Ethiopia; a Qualitative Exploration

Abstract: Background Novel Coronavirus is a global pandemic affecting all walks of life and it significantly changed the health system practices. Pharmacists are at the front line and have long been involved in combating this public health emergency. Therefore, the study was aimed to explore pharmacy preparedness and response to prevent and control coronavirus disease 2019 (COVID-19). Methods A qualitative study was conducted in six pharmacies in Aksum, Ethiopia in May, 2020. We conducted six in-depth interviews with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although early detection and prevention of onward transmission significantly reduce the burden of COVID-19 [2,4], most African countries are much less prepared for the effective point of entry, screening, monitoring of vacationers, and treatment in the case of the contagious virus [5,6]. According to the WHO report, the number of COVID-19 cases will be increasing in the coming era, if not improving the level of preparedness of healthcare providers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although early detection and prevention of onward transmission significantly reduce the burden of COVID-19 [2,4], most African countries are much less prepared for the effective point of entry, screening, monitoring of vacationers, and treatment in the case of the contagious virus [5,6]. According to the WHO report, the number of COVID-19 cases will be increasing in the coming era, if not improving the level of preparedness of healthcare providers [5].…”
Section: Introductionmentioning
confidence: 99%
“… 30 A study in Ethiopia showed that necessary pharmacy services have been rendered to all clients but drugs and medical supplies were scarce. 31 If the system fails to achieve this, it will increase the sick leave from the institution, 32 but in our institution, it’s made a little to protect the staffs, in Debre Tabor Hospital one health professional left the job due to fear of contracting the disease.…”
Section: Discussionmentioning
confidence: 99%
“…All these challenges to healthcare workforce in the midst of COVID‐19 have been documented frequently in the international literature, particularly from resource deprived nations with strained healthcare system. 5 , 15 , 29 , 30 , 46 , 48 To this end, Pakistani healthcare regulators need to act in tandem with developed countries 3 , 6 , 7 , 8 , 9 , 10 and strive towards advanced trainings accompanied by financial support for pharmacy sales staff. 5 Moreover, the government should intend to provide pharmacy staff with COVID‐19 protection packs, as provided by the UK government.…”
Section: Discussionmentioning
confidence: 99%